A Semitransparent Nitride Photoanode Responsive up to λ=600 nm Based on a Carbon Nanotube Thin Film Electrode. Issue 7 (17th April 2019) - Akagi, Daijiro; Kageshima, Yosuke; Hashizume, Yuta; Aoi, Shigeki; Sasaki, Yutaka; Kaneko, Hiroyuki; Higashi, Tomohiro; Hisatomi, Takashi; Katayama, Masao; Minegishi, Tsutomu; Noda, Suguru; Domen, Kazunari
Abstract: The development of semitransparent photoanodes is required for the construction of tandem photoelectrochemical (PEC) water splitting cells incorporating photocathodes. However, the poor stability of transparent conductive oxides at high temperatures hampers the growth of non‐oxide photoanodes with intense visible light absorption. In this work, semitransparent Ta3 N5 thin film photoanodes were prepared on quartz glass substrates coated with carbon nanotubes (CNTs) by sputtering and thermal nitridation. This process makes use of the high thermal and chemical stability as well as the tunable conductivity and transmittance of CNT substrates. The photoanodic current produced by these Ta3 N5 photoanodes at negative potentials is also enhanced by surface modification with Mg species. Conductive semitransparent CNT substrates such as these will assist in the development of new tandem PEC cells for water splitting. Abstract : Into the red : Semitransparent Ta3 N5 thin film photoanodes were prepared on quartz glass coated with carbon nanotubes (CNTs). The photoanodic current of the Ta3 N5 was enhanced by surface modification with Mg species. These CNT‐based photoanodes could be employed as top electrodes in tandem photoelectrochemical cells.